Internal fields of soot fractal aggregates - Berg, Matthew J.; Sorensen, Christopher M. (My University, 2013)
This work uses the discrete dipole approximation (DDA) to examine the internal electric field within a simulated carbon soot fractal aggregate in fixed and random orientations. For fixed orientations, deviations of the internal field magnitude up to ±50% from that assumed by the Rayleigh–Debye–Gans Approximation (RDGA) are found. Given the refractive index of the aggregate monomers and conditions for the validity of the approximation, such large deviations are no surprise. Yet despite this deviation, the far-field scattered intensity from such aggregates agrees surprisingly well with that described by the RDGA. Moreover, if the average over an ensemble of many random aggregate-orientations is calculated, both the DDA and RDGA scattered intensities obey the well-known power-law functionality in terms of the scattering wave vector and show a forward-angle intensity-maximum proportional to the square of the number of monomers. The explanation for this lies in the over and under estimations made by the approximation of the internal field, which apparently mostly cancel upon integration to yield the scattered intensity. It is shown that this error cancellation is related to the fractal structure of the aggregate and that the agreement between the DDA and RDGA improves with aggregates of increasing size provided the fractal dimension is less than two. Overall, the analysis suggests that both the special fractal character of the aggregate and its orientational averaging is important to account for the experimentally observed validity of the RDGA despite its poor description of the internal fields.
Keywords: Scattering theory; Scattering, particles; Scattering, stimulated; Aerosol and cloud effects; Aerosols; Scattering, polarization